Traditional food a taste of Korean life - Koehler, Robert; Lee, Jin-hyuk; Mouat, Colin A.; Jackson, Ben; Hyun-young, Jung (Seoul Seoul Selection, 2010)
This book examines the historical, nutritional, philosophical and cultural background of the Korean cuisine.
"The content of this series is based on the material published in Koreana, the Korea Foundation's full-color quarterly featuring in-depth coverage of various aspects of Korea's cultural themes"--Cover flap.
Includes bibliographical references (pages 124-125).
Keywords: Food habits -- Korea